Octanoate Alleviates Dietary Soybean Oil-Induced Intestinal Physical Barrier Damage, Oxidative Stress, Inflammatory Response and Microbial Dysbiosis in Large Yellow Croaker (Larimichthys Crocea) - Zhang, Zhou; Tang, Yuhang; Fang, Wei; Cui, Kun; Xu, Dan; Liu, Guobin; Chi, Shuyan; Tan, Beiping; Mai, Kangsen; Ai, Qinghui (Frontiers in Immunology, 2022)
Octanoate is a type of classical medium-chain fatty acids, which is widely used to treat neurological and metabolic syndrome. However, the specific role of octanoate in repairing intestinal health impairment is currently unknown. Therefore, we investigated whether dietary octanoate repaired the intestinal damage induced by surplus soybean oil in Larimichthys crocea. In this study, dietary octanoate alleviated abnormal morphology of the intestine and enhanced expression of ZO-1 and ZO-2 to improve intestinal physical barrier. Further, dietary octanoate increased antioxidant enzymic activities and decreased the level of ROS to alleviate the intestinal oxidative stress. Dietary octanoate also attenuated the expression of proinflammatory cytokines and the polarity of macrophage to reduce the intestinal inflammatory response. Moreover, the result of intestinal microbial 16S rRNA sequence showed that dietary octanoate repaired the intestinal mucosal microbial dysbiosis, and increased the relative abundance of Lactobacillus. Dietary octanoate supplementation also increased the level of acetic acid in intestinal content and serum through increasing the abundance of acetate-producing strains. Overall, in Larimichthys crocea, dietary octanoate might alleviated oxidative stress, inflammatory response and microbial dysbiosis to repair the intestinal damaged induced by surplus soybean oil. This work provides vital insights into the underlying mechanisms and treatment strategies for intestinal damage in vertebrates.